ENHANCING STUDENTS SPEAKING SKILL IN FACING THE REVOLUTION ERA 4 0 - Paranduk, Rida; Rombepajung, Paula; Karisi, Yofri (Journal of English Culture, Language, Literature and Education, 2021)
Many people think learning a language is easy because they assume we are using the language every day Learning a language is not just being able to communicate with the language but also know and understand the meaning contained in the word or phrase that pronounced In study languages especially English most of the students experiencing difficulty in speaking or talking Difficulty talk is usually caused by the difficult to express ideas orally limited vocabulary limited knowledge of grammar so it is difficult to talk with the correct rules limited ability to properly pronounce vocabulary pronounciation so it is difficult to pronounce a word with true the lack of courage to speak out because of fear of being wrong To facilitate the ability to speak speaking there are some pretty effective way to try among them: expand the vocabulary read aloud get to know the simple English read English conversation English listening to English songs watching English movies love the subjects English In this paper also discussed methods teaching role play and media pictorial story to improve the ability of English speaking students < p>